Tinjauan Yuridis Pengusaha yang Menolak Permohonan Pensiun Dini Pekerja dalam Perspektif Regulasi HAM Nasional - Adinda Rizqy Amalia; Wahyudi, Eko (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Every human being has fundamental rights from birth, including the right to life and work. Work is a means for individuals to sustain their livelihood and achieve personal goals. Upon achieving these goals, some workers choose to apply for early retirement. However, requests for early retirement are often rejected by employers, which can be considered a violation of human rights, particularly workers' rights to fair treatment at work. This study aims to legally analyse the rejection of early retirement by employers based on national human rights regulations using qualitative methods. Based on national regulations, such rejection, especially if stipulated in government regulations, collective labour agreements, or employment agreements, has the potential to violate workers' human rights, such as the right to personal freedom, the right to improve their standard of living, and the right to self-development.